Proteção a mulheres idosas em situação de violência no Núcleo Especializado dos Direitos do Idoso e da Pessoa com Deficiência (NEDIPED): um estudo de caso - Saiki, Elizabete (2017)
The objective of this study, based on an investigation that articulates violence with female aging, is to deepen the debate on issues related to the right to protection and security, in order to contribute to a in-depth discussion on the field of Social Gerontology and a qualified training of agents of the Public Defender's Office so that the care provided to elderly women in situations of violence can be even more effective. This work is justified since the achievement of longevity - a remarkable contemporary fact - must be analyzed from different angles, including one that brings the drama of violence. After all, current statistics show that the number of elderly in situations of violence in Brazil and in the world is increasing. I understand that scientific research can do much to change this reality. In this perspective, as a professional directly involved in guaranteeing rights, I have noticed the need to go beyond statistical data to investigate the factors that have responded to this reality. It’s a qualitative and exploratory research, having as subject an elderly woman in a situation of violence, attended by this researcher as social worker in the Public Defender's Office of the State of São Paulo. The recent case (2016) was chosen because it brought to light important issues relating to social violence. Besides this woman, one of their relatives and the professional colleagues of the Public Defender's Office of the State of São Paulo (who work in the areas of Psychology and Law) who accompanied this situation are also subjects of this research. The method used was the "Case Study", in which was chosen the “life history", as well as documentary research and semi-directive interview. In the analysis of the data collected in the field research were used concepts discussed in the bibliographic review on the subject in question. The results reveal the need to expand the role of services aimed at the elderly, qualification of professionals for a qualified hearing of victims and aggressors, as well as technical supervision of professionals